Osobliwości leksykalne w polemicznych utworach Marcina Czechowica = Lexical peculiarities in the polemical works of Marcin Czechowic - Hawrysz, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the study is to present selected lexical peculiarities extracted from the works of Marcin Czechowic, an active and influential Arian activist during the Reformation, and a long-time leader of of anti-Trinitarians in Lublin. The analyzes provide an opportunity to supplement knowledge about Czechowic`s idiolect, as well as to formulate several observations about the use of words and language in the era of religious discussions. The reasons for the appearance of lexical innovations included pragmatic considerations: the profile of creativity (they were a tool in a polemical clash), the identification of the anti-Trinitarian religious camp also at the level of colloquial lexis.
Keywords: Czechowic, Marcin (1532-1613); osobliwości leksykalne; Reformacja; polemika religijna - 16 w.; lexical peculiarities; reformation; religious polemics